Optoelectronic Performance Analysis of Low-Energy Proton Irradiation and Post-Thermal Annealing Effects on InGaAs Solar Cell - Zhuang, Y.; Aierken, A.; Lei, Q. Q.; Fang, L.; Shen, X. B.; Heini, M.; Guo, Q.; Guo, J.; Yang, X.; Mo, J. H.; Fan, R. K.; Li, J.; et al. (Frontiers in Physics, 2020)
The electrical and spectral properties of 150 KeV proton irradiated MBE grown In0.53Ga0.47As single junction solar cell and its post thermal annealing properties were investigated. Both simulation and experimental methods were applied to analyze the irradiation-induced displacement damages and degradation mechanism of cell performance. The results show that most protons would penetrate through In0.53Ga0.47As emitter and stop in base region causing different extent degradation of electric and spectral properties. When proton fluence were 1E12 and 5E12 p/cm2, the remaining factor of Isc, Voc, Pmax and FF were degraded to 0.790, 0.767, 0.558, 0.921 and 0.697, 0.500, 0.285, 0.817, respectively. And severer degradation of short wavelength than long wavelength of the solar cell spectral response was observed. After annealing treatments, the normalized Isc, Voc, Pmax and FF, significantly recovered from 0.697, 0.500, 0.285 and 0.817 to 0.782, 0.700, 0.499 and 0.912 (fluence: 5×1012 p/cm2), and the irradiation-induced defects in whole emission area and part of the base area were annihilated, so the observed recovery of short wavelength of the solar cell was greater than long wavelength.